Performing More-Than-Human Corporeal Connections in Kiki Smith’s Sculpture - Stępień, Justyna (Text Matters: A Journal of Literature, Theory and Culture, 2021)
The article examines work by contemporary American artist Kiki Smith, who proposes a future in which human and nonhuman bodily borders merge. The artist’s contribution to the more-than-human artistic entanglements is juxtaposed with Joseph Beuys’s artistic manifesto from 1974 which proposes, among other things, an attempt to get outside of the represented human towards the asignified ahuman. In Kiki’s sculpture, both human and nonhuman animals undergo constant morphogenesis, becoming hybrid forms far beyond the human-social paradigm, implying that the human and nonhuman binary, due to the exchange of affective entanglements, is no longer valid in the heyday of techno-scientific development. The analyzed work shows that both human and nonhuman bodies are raw materials not separated from one another but always interconnected with the world and its ongoing material processes. Thus, the article emphasizes that it is only through the transgression of the human and nonhuman border that one can acknowledge the more ethical and political ways of cooperation needed for the appreciation of the multispecies dimension of our world and its survival.